Research on Pump Primers for Friction Reduction of Wet-Mix Shotcrete Based on Precreating Lubricating Layer - Guoming Liu; Lianjun Chen; Weimin Cheng; Yanan Huang (Advances in Materials Science and Engineering)
Wet-mix shotcrete has lower water content even though looking wet which is generally less than 8% of total content. The inner surface of pipes will absorb water from fresh concrete to wet itself if concrete pump primers is not pumped early; meanwhile, the saturated concrete is transformed into the unsaturated concrete, and pipe blockage often occurs. In order to minimize the loss of water and wet pipes, a new type of pump primers was developed to precreate the lubricating layer that is one of the most dominant factors in determining the pumping capability, which would provide a cost-effective replacement for premium priced cement-based primers. Experiments were conducted to measure the viscosity, stability, and strength of mix solution during development stage. The optimal formula was obtained by orthogonal matching tests with 0.5% sodium stearate, 0.75% xanthan gum, 0.3% polyacrylamide, and 0.4% blender (mass ratio related to mix water). The pressure drop reduction of new primers was larger than that of common primers.